PHYSIOLOGICAL RESPONSES OF WORKERS TO OCCUPATIONAL STRESSES IN DARY INDUSTRY - DESA, M.J.K.; SAWANT, V.A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Industrial occupational hazards, stress, lack of safety measures, lack of healthy work place environment and welfare schemes are affecting the safety and health of the industrial workers. Dairy industry is one of the oldest and largest industries in the world. Maharashtra is one of the leading states in dairy industry and has provided employment to large number of people. Kolhapur Dudh Utpadak Sangh Ltd. operates dairy plant at Gokul Shirgaon Industrial estate. It is famous as Gokul. The study carried out in various sections in this dairy plant showed the occupational hazards and stress caused due to noise, vibration, inadequate illumination, heat, cold, dust, chemical hazards like exposure to ammonia gas, shift work, freak accidents and ergonomic hazards caused due to wrong body postures during work, faulty work place design. A healthy and scientifically designed work place and work conditions increase the efficiency of workers and productivity of the industry. The present research intends to evaluate the occupational stresses and hazards in dairy plant workers of Gokul dairy. A systematic, scientific methodological study was carried out to achieve perfection and authenticity in the research work.